Risk-based decision-making for the management of structural assets. - Roberts, Caroline (Cranfield University, 1999)
This thesis investigates the benefit of risk-based decision methods in engineering decisions. A thorough literature review identified the major issues and limitations in current methods. Consequently a more comprehensive model was developed to account for the complexities of real life decision-making. The enhancements introduced to the model include identifying and evaluating stakeholder influences, decision objectives, criteria and preferences between criteria and decision outcomes. Monitoring and controlling important parameters during implementation is also included to ensure objectives are met and risks controlled. Tools and techniques were identified to support decision-making within the new model. The research focuses on how available techniques can improve engineering decision-making. The model was applied to four case studies analysing real life, "live" decision problems in bridge management and pipeline management. These confirmed the relevance and importance of the model enhancements. The practicality of the methods, their benefits and limitations were evaluated such that the proposed model was enhanced further. The enhanced model was shown to bring enhanced understanding to all four case studies and made the decisions more rational, thorough and auditable. The fifth case study reviewed how unsupported decisions are currently made within the sponsoring company. This involved a detailed desktop analysis of past projects and interviews with senior engineers and provided further evidence, which emphasised the value of using the decision model. General guidelines were developed based on the case study experiences to help the decision-maker identify the level of analysis required for different types of decision problems. These were defined as applicability matrices. The benefit of using a third party facilitator in each of the case studies was identified in terms of the roles of leader, liaison, disseminator, spokesman and disturbance handler. The balance between these five roles through the stages of the decision process was found to be important to ensure the facilitator does not dominate the decision.